Comparative Analysis of the Structure and Function of AAA+ Motors ClpA, ClpB, and Hsp104: Common Threads and Disparate Functions - Duran, Elizabeth C.; Weaver, Clarissa L.; Lucius, Aaron L. (Frontiers in Molecular Biosciences, 2017)
Place Holder